A translation into modern prose of Chauser's "Knight's Tale." - Allentharp, Cecile (My University, 1907)
Introduction: Once as old stories tell us there was a duke called Theseus who was lord and governor of Athens. In his time there was no greater conqueror under the sun than he. He had won many a rich country; with his wisdom and chivalry he conquered all the kingdom of the Amazon which was once called Scithia, and had then married the queen Hippolita and brought herwith much glory and great festivity home with him into his own country. He also brought her young sister Emilia. Thus with victory and music this noble duke rode with all his host into Athens. If it were not too long I certainly would tell you how the kingdom of the Amazon was conquered by Theseus and by his chivalry,and of the great battle for once between the Athenians and the Amazons; and how Hippolita the fair queen of Scithia was besieged, and of the feast at her wedding and of the tempest at her home coming; but all this I must forbear. I have, God knows, a large field to plow and the oxen to my plow are weak; the remainde of my tale is long enough. I will not take up all the time, but let each companion tell his tale and see who wins the supper, so where I left off I will again begin.
Citation: Allentharp, Cecile. A translation into modern prose of Chauser's "Knight's Tale.". Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Knight's Tale; Literature; Ancient Literature; Modern Translation; Theses